Primary or Redo Posterior Sagittal Anorectoplasty without a Stoma: To Feed or Not to Feed? - Reck-Burneo, Carlos A.; Skerrit, Clare; Dingemans, Alexander; Lane, Victoria A.; Sanchez, Alejandra Vilanova; Weaver, Laura; Wagner, Andrea; Jenkins, Nicole; Wood, Richard J.; Levitt, Marc A. (European Journal of Pediatric Surgery, 2019)
Introduction Repair of anorectal malformations (ARMs), primarily or with a reoperation, may be performed in certain circumstances without a diverting stoma. Postoperatively, the passage of bulky stool can cause wound dehiscence and anastomotic disruption. To avoid this, some surgeons keep patients NPO (nothing by mouth) for a prolonged period. Here, we report the results of a change to our routine from NPO for 7 days to clear fluids or breast milk.Materials and Methods After primary or redo ARM surgery, patients given clear liquids were compared to those who were kept strictly NPO. Age, indication for surgery, incision type, use of a peripherally inserted central catheter (PICC) line, and wound complications were recorded.Results There were 52 patients, including 15 primary and 37 redo cases. Group 1 comprised 11 female and 15 male patients. The mean age at surgery was 4.9 years (standard deviation [SD]: 2.3). There were 8 primary cases and 18 redo cases. Twelve (46.6%) received a PICC line. The average start of clear liquids was on day 5.3 (SD: 2.2) after examination of the wound, and the diet advanced as tolerated. The first stool passage was recorded on average on day 2.3 (SD: 1.3). Four minor wound complications and no major wound complications occurred.Group 2 comprised 14 females and 12 male patients. The mean age at surgery was 3.5 (SD: 2.4) years. There were 7 primary and 19 redo cases. One (3.8%) patient required a PICC line. A clear liquid diet was started within 24 hours after surgery. A regular diet was started on average on day 5.8 (SD: 1.3). The first stool passage was recorded on an average of day 1.6 (SD: 0.9). Three minor wound complications occurred; however, there was no significant difference between the two groups (SD: 0.71). One major wound complication occurred. However, there was no significant difference in major wound complications between the groups (SD: 0.33).Conclusion No increase in wound problems was noted in children receiving clear liquids or breast milk compared with the strict NPO group, and PICC line use was reduced. We believe this change in practice simplifies postoperative care without increasing the risk of wound complications.
Keywords: PSARP; NPO; stoma; anorectal malformation